1998
DOI: 10.1021/js970377b
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Local Inhibition of Intestinal Adenosine Deaminase (ADA) by eryfftro-9-(2-Hydroxy-3-nonyl)adenine: Enhanced Oral Delivery of an ADA-Activated Prodrug for Anti-HIV Therapy

Abstract: Previous in situ perfusion studies in rat ileal segments have demonstrated that high concentrations (>40 microg/mL) of erythro-9-(2-hydroxy-3-nonyl)adenine (EHNA), a semitight binding inhibitor of adenosine deaminase (ADA), are effective in completely inhibiting the intestinal metabolism of 6-chloro-2',3'-dideoxypurine (6-Cl-ddP), an ADA activated prodrug of the anti-HIV agent 2', 3'-dideoxyinosine (ddI) designed for improved targeting to the central nervous system. However, the intestinal absorption of EHNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In this study, partial inhibition was obtained with DCF but full inhibition was obtained with EHNA. Further, the apparent K i of ADA present in the intestinal epithelium was determined in in situ perfusions in mesenteric cannulated rat ileal segments to be <5 nM using EHNA, 61 which strongly suggests that the ADA responsible for bioconversion of 6-Cl-ddP in the intestinal wall is ADA 1 . This is also consistent with the fact that ADA 1 constitutes 90-100% of the total ADA which is present intracellularly.…”
Section: Resultsmentioning
confidence: 96%
“…In this study, partial inhibition was obtained with DCF but full inhibition was obtained with EHNA. Further, the apparent K i of ADA present in the intestinal epithelium was determined in in situ perfusions in mesenteric cannulated rat ileal segments to be <5 nM using EHNA, 61 which strongly suggests that the ADA responsible for bioconversion of 6-Cl-ddP in the intestinal wall is ADA 1 . This is also consistent with the fact that ADA 1 constitutes 90-100% of the total ADA which is present intracellularly.…”
Section: Resultsmentioning
confidence: 96%
“…To corroborate this conclusion, we next examined the DNA incorporation of [ 15 N 5 ]-dA using the Ada inhibitor. By treating 293T cells with an Ada inhibitor erythro -9-(2-hydroxy-3-nonyl)­adenine (EHNA), , the signals of [ 15 N 4 ]-dA and [ 15 N 4 ]-dG in genomic DNA decreased by 75.0%–96.4% and 75.4%–96.8% (Figure B), respectively. Meanwhile, we observed the presence of [ 15 N 5 ]-dA in genomic DNA, but the signal of [ 15 N 5 ]-dA is less than 5% of that for dA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…At this low level (1 uM), the 2′-deoxycoformycin alone had no effect on virus replication; however, with a Ki of ~50 nM as an ADA inhibitor, its effect is likely at the level of adenosine deaminase. [20] The D-valyl ester prodrugs of vidarabine showed EC50 values comparable to vidarabine alone. It is unclear at this stage whether the antiviral activity of the prodrugs resulted from the prodrug itself or vidarabine derived by the hydrolysis of the amino acid ester moiety.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Significant levels of this enzyme are found in the intestinal mucosa,[20,21] which limits the effectiveness of oral vidarabine delivery. Previous studies suggested that 5′-hydroxy substituted vidarabine analogs were resistant to adenosine deaminase.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%